Carrier Effect in Development of Rifampin Loaded Proliposome for Pulmonary Delivery: A Quality by Design Study - Elahehnaz Parhizkar; Delaram Sadeghinia; Hamed Hamishehkar; Shadi Yaqoubi; Ali Nokhodchi; Shohreh Alipour (Tabriz University of Medical Sciences, 2022)
Purpose: Pulmonary tuberculosis (TB) is a worldwide life-threatening infection. Therecommended anti-TB regimen contains oral administration of classical first-line drugs suchas rifampin for 6-24 months which often leads to low patient compliance due to high adverseeffects; therefore, lung localized pulmonary delivery of anti-TB agents may be a suitablealternative. Proliposomes free-flowing powders are well-known carriers for lung delivery sincethey can form liposomes by hydration. Liposomes are safe and useful carriers for lung deliverydue to their phospholipid structure.Methods: Porous lactose and mannitol as proliposome carriers were prepared by spray dryingtechnique using sucrose and citric acid as templating agents. Design Expert® software wasused to develop forty formulations based on the porous and non-porous carriers, which werecharacterized with respect to their weight yield, density, and flowability. Rifampin-loadedhydrated liposomes were produced and evaluated for size, morphology, loading capacityand encapsulation efficiency. The optimized proliposomes in vitro release and aerosolizationproperties were evaluated. Solid-state analysis was confirmed by differential scanningcalorimetry (DSC).Results: Porous lactose surface area was 80 folds higher than non-porous one, respectively.Optimized porous-based proliposome indicated the acceptable aerosolization properties,including mass median aerodynamic diameter (MMAD) of 6.21 ± 0.36 μm and fine particlefraction (FPF) of 9.17 ± 0.18% with a fast rifampin release (80%) within one hour. DSC resultsproved that there was no change in the solid-state of rifampin during the production process.Conclusion: Hence, it seems; rifampin loaded inhalable proliposomes may be a suitable systemfor delivering liposomal rifampin into the lungs.